Social media marketing as promotion tools to promote new talents among students in Faculty of Music UiTM Shah Alam. / Nur Aina Sofea Mohamed Esa - Mohamed Esa, Nur Aina Sofea (2019)
This is a study on social media marketing as a promotion tools to promote new talents among students in Faculty of Music UiTM Shah Alam. Social media is very important to our life in this digitalization era. This research is to study the importance of social media use to the music industry and how social media can be a tools for promoting talents among music students. This study utilized quantitative method and the data were collected through survey questionnaire who represent music students from all departments in Faculty of Music. I have discovered that majority of the respondents are using social media as their platform to exposed their music or talent. It shows that social media is the new medium of platform to find a new talent and self-exposure for students to be an artist.